A personal leadership statement ﻿ (2023)
Leadership is vital for the adequate development of society. Therefore, strong leadership skills are required to be fostered among teachers since these individuals are responsible for effectively supporting, instructing, and mentoring future generations by providing them with both useful knowledge, as well as values and attitudes for a lifelong learning. This statement attempts to present a general perspective about leadership in educational contexts based on several authors along with a personal definition of it from the viewpoint of future teacher leaders. Moreover, exploring the relevance of enhancing teacher leadership skills through empowerment is also a main concern of this writing.